Assessing the effect of loyalty program benefits in satisfaction- loyalty relationship: evidence from Malaysia - Nor Asiah Omar,; Suhaily Mohd Ramly,; Syed Shah Alam,; Muhamad Azrin Nazri, (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study aimed at examining the relationship among program benefi ts (utilitarian/monetary, hedonic, and symbolic), program satisfaction, and loyalty (program loyalty and store loyalty) in the retail context in Malaysia. A total of 300 questionnaires were collected via convenience sampling from program members of hypermarkets and superstores in Malaysia. A structural equation model that assessed the relationship between the proposed variables was tested using AMOS 20. The fi ndings revealed that of the three program benefi ts, utilitarian benefi ts and symbolic benefi ts were statistically signifi cant in infl uencing program satisfaction. In terms of loyalty, both hedonic and symbolic benefi ts were related to program loyalty and only hedonic benefi t was positively related to store loyalty.